Construction of Asy-Syahadatain's Epistimology - Iin Solikhin (Islamic Studies Journal, 2022)
The purpose of this study is to describe how the epistemology construction of ash-syahadatain. The method used in this research uses literature study. In history, humans have always been preoccupied with fundamental questions about themselves. The results of this study found that in discovering the truth of knowledge, Jama'ah Asy-Syahadatain uses the concept of what is called scientia sacra or sacred knowledge and is reflected in the concepts of reason, heart, and metabolism. As one (read: Tariqah) Jama'ah Asy-Syahadatain has certain practices, as well as the practice of worship, and respect for the ahlu bait.